Peran Manajemen Kemasyarakatan Dalam Usaha Pengembangan Madrasah Ibtidaiyah Swasta - Hanif Hanani; Giyoto Giyoto; Yusuf Rohmadi (Jurnal Ilmiah Ekonomi Islam, 2021)
The role of madrasas as models of Islamic education today is growing quite rapidly. It has even become an alternative institution for some Muslim families in educating their children. This is because madrasas are considered to provide two dimensions of Muslim scientific life between worldly and hereafter needs. Community participation in education development is an important issue in the National Education System Law no. 20 of 2003, a policy that involved the community in education programs and the birth of a school-based management (SBM) offer that gave relatively broad autonomy to schools and communities. In Chapter III article 8 it is stated that "the community has the right to participate in the planning, implementation, monitoring and evaluation of educational programs". This indicates that the existence and participation of the community is increasingly recognized and needed in the development and development of education, especially Islamic education. This research method is a qualitative method with a phenomenological approach. The research results of the current school Public Relations Program are very important, related to changes in the social, political, legal, and economic framework of the community. Management of competency development in educators is part of a human resource development strategy which is a basic need in an organization, both formal and non-formal. . This is an investment for the organization in this case the madrasa, which will have implications for the development of a nation's human resources. In Increasing Public Interest In Islamic Educational Institutions. The results of the study: the function of public relations in educational institutions is to grow and develop harmonious relationships through communication using media between schools and the community, both internally (lecturers / teachers, employees, students / students) and externally (parents, communities, and institutions). .